2018
DOI: 10.1002/suco.201700255
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of using treated industrial wastewater to produce concrete

Abstract: We studied the feasibility of reusing of treated industrial wastewater from Tehran Refinery and Distribution Company in the production of concrete. Three types of concrete samples with 350, 400, and 450 kg/m 3 of cement were made with two different types of water, including drinking water and treated industrial wastewater. The results indicated that the use of treated industrial wastewater in the production of concrete instead of drinking water resulted in a 6.9% decreased in compressive strength of cement san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 15 publications
3
40
0
1
Order By: Relevance
“…Also, as observed in Table 9, applying the treated wastewater instead of tap water in the different concrete mix designs, the 30‐min water adsorption increased between 0.4 and 1% at 28 days. Asadollahfardi et al 12 and Asadollahfardi and Mahdavi 13 confirmed our results, but they studied on conventional concrete; however, we worked on SCCs. As a general, using treated wastewater decreased durability of different concrete mix designs.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Also, as observed in Table 9, applying the treated wastewater instead of tap water in the different concrete mix designs, the 30‐min water adsorption increased between 0.4 and 1% at 28 days. Asadollahfardi et al 12 and Asadollahfardi and Mahdavi 13 confirmed our results, but they studied on conventional concrete; however, we worked on SCCs. As a general, using treated wastewater decreased durability of different concrete mix designs.…”
Section: Resultssupporting
confidence: 88%
“…This SEM image confirmed decreasing the compressive strength of concrete samples containing the treated wastewater related to concrete samples using drinking water. The same results of SEM were achieved by Asadollahfardi et al and Asadollahfard and Mahdavi et al 13 The difference between their studies and present work is we studied on SCCs instead of conventional concrete.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Since the chemical composition of WW is different from that of tap water, reactions and more gas bubbles may be generated. Based on the studies of Saxena and Tembhurkar [24,27], Asadollahfardi and Mahdavi [31] and Yahyaei et al [32], the air content of concrete increases (2-34%) with the use of WW, unless it has been treated.…”
Section: Air Contentmentioning
confidence: 99%